Some variables affecting the vocational choices of PCAT students - Chinwong, Nikom 1940- (s.n.], 1972)
This survey sought to determine the variables affecting the vocational choices of PCAT students. The variables were classified into five categories: personal data of student, educational data, social data, data on the hobbies and extra curricular activities, and data on the part-time work.